2022
DOI: 10.3389/fcvm.2022.863248
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Bioinformatics Analysis Based on Public and Second-Generation Sequencing Transcriptome Data: A Study on the Diagnostic Value and Potential Mechanisms of Immune-Related Genes in Acute Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is one of the most serious cardiovascular diseases worldwide. Advances in genomics have provided new ideas for the development of novel molecular biomarkers of potential clinical value for AMI.MethodsBased on microarray data from a public database, differential analysis and functional enrichment analysis were performed to identify aberrantly expressed genes in AMI and their potential functions. CIBERSORT was used for immune landscape analysis. We also obtained whole blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A recent study found that expression of let-7 was significantly downregulated after MI, targeting TGFBR3 through the activation of the p38 MAPK pathway. 11 The let-7-TGFBR3-p38 MAPK signaling may play a significant role in cardiomyocyte apoptosis post-MI, making TGFBR3 a potential therapeutic target and biomarker for MI. A study revealed that S100A12, 12 enriched in the Mitogen-Activated Protein Kinase (MAPK) signaling pathway, NF-κB signaling pathway, and inflammatory response pathway, is associated with the onset and progression of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that expression of let-7 was significantly downregulated after MI, targeting TGFBR3 through the activation of the p38 MAPK pathway. 11 The let-7-TGFBR3-p38 MAPK signaling may play a significant role in cardiomyocyte apoptosis post-MI, making TGFBR3 a potential therapeutic target and biomarker for MI. A study revealed that S100A12, 12 enriched in the Mitogen-Activated Protein Kinase (MAPK) signaling pathway, NF-κB signaling pathway, and inflammatory response pathway, is associated with the onset and progression of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune cells and their cytokines not only contribute to the immediate response to myocardial injury but also influence subsequent healing and remodeling processes [ 7 ]. Recent studies have highlighted IRGs as potential biomarkers for early AMI diagnosis and outcome prediction [ [8] , [9] , [10] ]. However, a knowledge gap persists regarding the intricate relationship between these IRGs and clinical outcomes in STEMI patients.…”
Section: Introductionmentioning
confidence: 99%